Compressional and Shear Wave Pre-Stack Analysis of Gas-Hydrate Resources in the Makran Accretionary Prism. Issue 2 (June 2014) - Salehi, Ehsan; Javaherian, Abdolrahim; Pour, Majid Ataee; Khah, Nasser Keshavarz Faraj; Khoshdel, Hossein
The method of amplitude-variation-with-angle (AVA) inversion was applied to estimate hydrate and gas saturations along bottom simulating reflector (BSR) at the Makran Accretionary Prism, Iran. Two AVA approximations were used to calculate their corresponding AVA attributes were compared to each other. To investigate the accuracy of each attribute and measure its probable deviation from actual values, the AVA inversion was first applied to 30 sets of synthetic models. Synthetic results showed that uncertainties involved in two input parameters of inversion, density/velocity relation and Vs/Vp, causes an error in the estimated attributes which result in unrealistic estimations of hydrate and gas saturations. To diminish the adverse impact of this uncertainty on the field data, a simulated annealing (SA) approach was suggested to derive the Vs/Vp in a number of locations. These values were then interpolated to provide a model of estimated Vs/Vp in other locations. Quantification of hydrate and gas saturations was based on a correlation between the AVA inverted attributes and the rock physics derived attributes (RPDA). The RPDAs were generated using the effective medium theory (EMT) rock physics modeling applied on models with assumed input parameters such as lithology and porosity. Corresponding saturations of the nearest RPDA to a pair of AVA inverted attributes were considered as the hydrate and gas saturation for that specific location. The quantification assessment indicated 11%, 14% and 15% hydrate saturations in the vicinity of the BSR for locations with low, intermediate and high post-stacked amplitude, respectively. The saturation of the free gas was also estimated as less than 1%, 2% and 3% with the same order as above, respectively.